1988
DOI: 10.2307/1590988
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometry and Vitamin D Metabolism of Valgus-Varus Deformity in Broiler Chickens

Abstract: Vitamin D metabolite levels and tibiotarsal histomorphometric characteristics were determined in 49-day-old male broilers. Valgus-varus bone deformity was present in 5.2% and tibial dyschondroplasia (TD) in 3% of these broilers, which were raised on floor litter under seemingly normal nutritional, space, and lighting conditions. No significant weight differences were observed between normal and lame broilers. The plasma levels of 25-OH-D were the same in lame and normal broilers. However, 1,25-(OH)2D plasma le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Diaphyseal crosssections were also analysed with the Visilog software in order to quantify cortical and marrow areas and diameters. The cortex was divided into a peripheral active zone, a mature zone and a resorption zone [14,17].…”
Section: Methodsmentioning
confidence: 99%
“…Diaphyseal crosssections were also analysed with the Visilog software in order to quantify cortical and marrow areas and diameters. The cortex was divided into a peripheral active zone, a mature zone and a resorption zone [14,17].…”
Section: Methodsmentioning
confidence: 99%
“…The porosity (area of lacunae/cortical area, %) was measured in 4 quadrants of cortical bone: anterior, lateral, medial and posterior. A second evaluation of porosity was obtained by measuring the thickness of active, dense and endosteal zones in the cortex of each quadrant (Newbrey et al, 1988). Mineral apposition rate (MAR, m m/day;Par tt et al, 1987) was evaluated in 5 osteones from each previously described quadrant.…”
Section: Histologymentioning
confidence: 99%
“…Comparisons between healthy and lame birds show modi cations of bone cortex: hypertrophy of the diaphysial cortex (Itakura and Yamagiwa, 1970;Cruickshank and Sim, 1986), altered con gurations of tibial cross-sections (Newbrey et al, 1988) and even reduced ash content (Leterrier and Nys, 1992a). However there is no evidence that these changes were present at the initial stage of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Two principal forms of skeletal abnormalities that have been defined as areas of concern (Riddell, 1981) are defective bone formation or osteodystrophy and abnormal cartilage formation, such as that seen in dyschondroplasia. The incidences of bone deformity attributed to abnormal cartilage formation, in the form of tibial dyschondroplasia, and osteodystrophy are considered to be, respectively, 1 to 3% and 5% (Riddell et al, 1971;Poulos et al, 1978;Newbrey et al, 1988). However, these definitions can become blurred as tibial dyschondroplasia can be linked to defective bone formation (Lynch et al, 1991).…”
Section: Young Rapidly Growing Broiler Chicksmentioning
confidence: 99%
“…Some studies indicate that broilers with bone deformities have delayed cortical bone formation (Newbrey et ah, 1988), poor metaphyseal modelling (Dammrich & Rodenhoff, 1970;Itakura & Yamagiwa, 1970, 1971 and decreased plasma 1,25 dihydroxycholecalciferol levels (Newbrey et al, 1988), suggesting that in some birds with deformities there is an overall reduction in bone formation and turnover. As prostaglandins are local mediators of skeletal remodelling it has been suggested that deficient prostaglandin metabolism, induced by nutrition or activity, could be a cause of bone deformities (Newbrey et al, 1988). However, lower metabolic activity in disabilitated birds with severe deformities appears the more likely cause of reduced bone formation and turnover.…”
Section: Torsional (Rotational) and Valgus/varus (Angular) Deformitymentioning
confidence: 99%